Different degrees of maternal Ureaplasma colonization and its correlation with bronchopulmonary dysplasia in <32 weeks' preterm infants - Jiyoung Chun; Sang Hoon Chun; Yea Seul Han; Tae-Jung Sung (Pediatrics and Neonatology, 2019)
Background: Ureaplasma spp. is a known risk factor for bronchopulmonary dysplasia (BPD). However, little is known about the effect of different degrees of maternal Ureaplasma colonization and their adverse outcomes. Hence, the aim of this study was to determine the effects of different degrees of maternal Ureaplasma colonization on BPD. Methods: A retrospective cohort study of preterm infants delivered at <32 weeks' gestational age (GA) was performed. The infants were divided according to maternal Ureaplasma status as follows: high-colonization (≥104 CCU/ml, UUH), low-colonization (<104 CCU/ml, UUL), and noncolonization (controls). Subgroup analysis according to neonatal respiratory Ureaplasma (n-UU) was also performed to evaluate vertical transmission. Results: In total, 245 infants were included in this study (UUH = 105, UUL = 47, controls = 93). The rates of preterm labor and histological chorioamnionitis were significantly different. The rate of BPD was significantly high in UUH (P = 0.044). The transmission rate of n-UU colonization was 36% in UUH and 32% in UUL (P = 0.609). The rate of BPD was 78% in n-UU (+) of UUH but 43% in n-UU (−) of UUL (P = 0.027). Conclusions: High-degree colonization of maternal Ureaplasma was associated with preterm labor, histological chorioamnionitis, and neonatal BPD. The incidence of BPD was significantly higher in Ureaplasma-colonized infants born to women with high-degree colonization. Key Words: bronchopulmonary dysplasia, colonization, preterm infant, ureaplasma species